Nonorthogonal Two-Dimensional Cutting Patterns - Rinnooy Kan, A. H. G.; De Wit, J. R.; Wijmenga, R. Th. (Management Science, 1987)
The optimal way to cut a number of pieces from a reel is usually studied under the assumption that each piece has one of its sides parallel to the reel edge. If the material to be cut is homogeneous, it may be attractive to consider patterns in which certain pieces appear in an intermediate, tilted position. Certain properties of a class of such nonorthogonal cutting patterns axe derived that make it possible to allow for tilting in a simple manner. Substantial savings may thus be realised at the expense of a modest increase in computational effort.